The Potential of Jamblang Root or Java Plum (Syzygium cumini) in Medicinal Uses: A Systematic Review - Anita Fajriyani; Anisah Fitriyani; Ridha Alisthipa Sephia; Hidayah, Himyatul (HM Publisher, 2023)
Jamblang root has long been used in traditional medicine as a natural remedy for various health conditions. This study aimed to present a systematic review to explore the potential of jamblang roots in the health sector. This study is a systematic literature review in which exploration was carried out literature from various reputable scientific publication databases. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Several studies have shown that jamblang root has anti-inflammatory properties that can help reduce inflammation in the body. In conclusion, jamblang root or java plum (Syzygium cumini) has the potential for anti-diabetic, anti-inflammatory, antioxidant, hepatoprotective, and astringent effects.